Ruang Leisure Perempuan : Kajian Tren Kafe sebagai Praktik Kemaslahatan Sosial di Era Keberlanjutan - Alvi Fauziyah; Cory Vidiaty (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
The phenomenon of increasing female activity in cafes shows a shift in lifestyle that is not merely consumptive, but also reflective and social. Cafes have now become leisure spaces where women express themselves, build relationships, and find emotional balance. This study aims to examine the trend of women utilizing cafes as a practice of social welfare in the era of sustainability. The approach used is descriptive qualitative based on secondary sources, with data in the form of news articles, lifestyle writings, and online media coverage of women's leisure behavior in Cirebon. This analysis was conducted to explore the social and spiritual values that emerge in these activities. The results of the study show that cafes serve as safe spaces for women to interact, share ideas, and restore mental energy. These activities reflect maqashid values such as Hifz al-nafs (preserving the soul) and Hifz al-'aql (preserving the mind), while contributing to the spirit of sustainability through the strengthening of gender equality and social welfare. The novelty of this research lies in its attempt to interpret women's leisure trends through the paradigm of social welfare, rather than simply as a modern lifestyle. These findings have important implications for the creation of a more inclusive, safe, and sustainable public space, while also opening up a new perspective that leisure activities can be part of achieving maqashid al-syari'ah in contemporary social life.